The Flexural Strength of Artificial Laminate Composite Boards made from Banana Stems - Achmad Jusuf Zulfikar (Budapest International Research and Critics University, 2020)
Wood is a forest product that is used as raw material for building construction. The increase in demand for wood causes damage to the environment and the ecosystem. Therefore, investigation is needed to find alternative materials that can replace the old wood. On the other hand, Indonesia is a banana tree producing country which in every harvest produces abundant waste of banana stems. In this study, an investigation will be made of artificial wood from banana stems. The purpose of this investigation is to obtain the flexural strength of artificial wood produced from banana tree trunks. Banana stems will be treated first in 1M NaOH solution. Making artificial wood using special printing tools and adhesives of acetate type. Flexural testing uses the ASTM D790 test standard. The results obtained that the average flexural strength of artificial wood is 3.14 MPa. This value is still much smaller when compared to the flexural strength of commercial wood, which is 87.21. However, artificial wood has the ability to absorb the load provided is better than commercial wood.